Trading Thalesians : what the ancient world can teach us about trading today - Amen, Saeed; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book mixes history on the ancient world with investment ideas for traders involved in financial markets today. It goes through ideas such as measuring risk, whether investors should try to outperform the market, Black Swans and ways of creating appropriate investment targets. It will appeal to professional traders and retail investors.
Keywords: Science